Advances in Intelligent Computing - Mandal, J. K.; Dutta, Paramartha; Mukhopadhyay, Somnath; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This edited volume on computational intelligence algorithms-based applications includes work presented at the International Conference on Computational Intelligence, Communications, and Business Analytics (CICBA 2017). It provides the latest research findings on the significance of computational intelligence and related application areas. It also introduces various computation platforms involving evolutionary algorithms, fuzzy logic, swarm intelligence, artificial neural networks and several other tools for solving real-world problems. It also discusses various tools that are hybrids of more than one solution framework, highlighting the theoretical aspects as well as various real-world applications.
Use of possibility measures for ranking of interval valued intuitionistic fuzzy numbers in solving multi-criteria decision making problems -- Optimization of Environmental-Economic Power Generation and Dispatch through GA based Multi-objective Bi-level Programming -- An Opposition Based Differential Evolution to Solve Multiple Sequence Alignment -- Swarm Intelligence Algorithms for Medical Image Registration: A Comparative Study -- Rough Kernelized Fuzzy C-Means based Medical Image Segmentation -- A Hybrid PSO-Fuzzy based Algorithm for Clustering Indian Stock Market Data -- Application of Artificial Immune System Algorithms for Intrusion Detection -- Genetic Algorithm-based Matrix Factorization for Missing Value Prediction -- GA-ARM Approach Towards Finding Rules of Occupational Accidents In a Steel Plant -- Brain signal based Biometric Identification using 1D-LGP and ANN -- On Energy Efficient Cooperative Spectrum Sensing using Possibilistic Fuzzy C-Means Clustering -- Type-2 Fuzzy Controller with Type-1 Tuning Scheme for Overhead Crane control -- A Spatial Domain Image Authentication Technique using Genetic Algorithm -- Control of Two-Axis Helicopter Model Using Fuzzy Logic -- Memetic Algorithm based Feature Selection for handwritten City Name Recognition.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence